Board expertise diversity and firm performance in sub-Saharan Africa: do firm age and size matter? - Felix Kwabena Danso; Michael Adusei; Beatrice Sarpong-Danquah; Kwadwo Boateng Prempeh (Future Business Journal)
Abstract Our study delved into an analysis of 128 public companies in Ghana, Kenya, and Nigeria to explore the influence of diversified board expertise on firm performance. We also investigated the impact of firm size and age on this relationship. Our results indicate that a varied blend of professional experts on corporate boards significantly boosts a company's ROA, although there is no significant effect when Tobin's Q measures firm performance. Nevertheless, we discovered that combining firm size and age negatively impacts the correlation between board expertise diversity and firm performance. Our findings support the significance of integrating agency, resource dependence, and convergence theories, implying that businesses can improve their financial performance by including an appropriate mix of expertise on their boards, especially for relatively younger small-sized firms. In contrast, more prominent and ageing firms may not see the same financial benefits. Consequently, we recommend that corporate executives and practitioners consider implementing board expertise diversity to enhance their firms' financial performance.